2023
DOI: 10.22541/au.169029006.64453530/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The phytoplankton of the Patagonian Shelf-Break Front

Abstract: Intense phytoplankton blooms in the Patagonian Shelf-Break Front (PSBF) in the southwest Atlantic Ocean (˜35°S-55°S) are responsible for making this large marine ecosystem one of the most productive and rich in resources and biodiversity of the Global Seas. This systematic review presents an up-to-date knowledge of the phytoplankton community composition, biomass and primary productivity along the permanent PSBF from temperate to subpolar latitudes. The interaction between wind stress, shelf waters, the steep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…There are scarce data on the nutrient conditions of the Patagonian shelf, mostly focused on the PSBF (Supporting information Table S2; Guinder et al 2023). Nutrients measured in this study (Supporting Information Table S2) are in agreement with the ranges reported in the literature, and show that in general dissolved inorganic nutrients increase from the shelf to the shelf‐break.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are scarce data on the nutrient conditions of the Patagonian shelf, mostly focused on the PSBF (Supporting information Table S2; Guinder et al 2023). Nutrients measured in this study (Supporting Information Table S2) are in agreement with the ranges reported in the literature, and show that in general dissolved inorganic nutrients increase from the shelf to the shelf‐break.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial heterogeneity of surface phytoplankton blooms and their governing factors in the Patagonian shelf have been studied mostly from satellite chlorophyll a (Chl a ) estimations and in a lesser extent from in situ measurements, as revised in Guinder et al (2023). Even less studied are the phytoplankton blooms in the transition across the 40°S parallel, a portion of the shelf which embraces the shallow area of El Rincón and the mid‐shelf and shelf‐break fronts, with a particularly complex hydrography (Guinder et al 2018; Ferronato et al 2021).…”
Section: Figmentioning
confidence: 99%